Inverse Design of Terahertz Optical Power Splitters Using the Particle Swarm Optimization Method - Goudarzi, Kiyanoush; Lee, Han eol; Kim, Doyoung; Park, Ikmo; Han, Haewook (Journal of Electromagnetic Engineering and Science, 2023)
This letter proposes 50:50 TE terahertz power splitters based on digitized metamaterials. The components are optimized using the particle swarm optimization algorithm. The digitized metamaterials are formed as a silicon slab with circular air holes atop a silicon dioxide substrate. The insertion losses of optimized structures containing air holes with a radius of 9 μm and air holes with different radii (9 μm and 7 μm) are less than 3.9 dB and 3.65 dB, respectively, over a frequency range of 0.87–1.09 THz. The footprint of the proposed devices is 400 μm × 350 μm. The devices have excellent characteristics, such as compactness, efficiency, all-dielectric properties, and compatibility with CMOS fabrication technologies, and can become vital components of most terahertz-wave routing circuits.
Keywords: Inverse Design; Optical Power Splitters; Particle Swarm Optimization; Silicon Photonics